Identification and Characterization of a Phase-Variable Element That Regulates the Autotransporter UpaE in Uropathogenic Escherichia coli - E. J. Battaglioli (American Society for Microbiology, 2018)
ABSTRACT Uropathogenic Escherichia coli (UPEC) is the most common etiologic agent of uncomplicated urinary tract infection (UTI). An important mechanism of gene regulation in UPEC is phase variation that involves inversion of a promoter-containing DNA element via enzymatic activity of tyrosine recombinases, resulting in biphasic, ON or OFF expression of target genes. The UPEC reference strain CFT073 has five tyrosine site-specific recombinases that function at two previously characterized promoter inversion systems, fimS and hyxS. Three of the five recombinases are located proximally to their cognate target elements, which is typical of promoter inversion systems. The genes for the other two recombinases, IpuA and IpuB, are located distal from these sites. Here, we identified and characterized a third phase-variable invertible element in CFT073, ipuS, located proximal to ipuA and ipuB. The inversion of ipuS is catalyzed by four of the five CFT073 recombinases. Orientation of the element drives transcription of a two-gene operon containing ipuR, a predicted LuxR-type regulator, and upaE, a predicted autotransporter. We show that the predicted autotransporter UpaE is surface located and facilitates biofilm formation as well as adhesion to extracellular matrix proteins in a K-12 recombinant background. Consistent with this phenotype, the ipuS ON condition in CFT073 results in defective swimming motility, increased adherence to human kidney epithelial cells, and a positive competitive kidney colonization advantage in experimental mouse UTIs. Overall, the identification of a third phase switch in UPEC that is regulated by a shared set of recombinases describes a complex phase-variable virulence network in UPEC. IMPORTANCE Uropathogenic Escherichia coli (UPEC) is the most common cause of urinary tract infection (UTI). ON versus OFF phase switching by inversion of small DNA elements at two chromosome sites in UPEC regulates the expression of important virulence factors, including the type 1 fimbria adhesion organelle. In this report, we describe a third invertible element, ipuS, in the UPEC reference strain CFT073. The inversion of ipuS controls the phase-variable expression of upaE, an autotransporter gene that encodes a surface protein involved in adherence to extracellular matrix proteins and colonization of the kidneys in a murine model of UTI.